1998
DOI: 10.2166/wst.1998.0528
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Norwalk virus, poliovirus 1 and coliphage MS2 by monochloramine disinfection of water

Abstract: The reduction of Norwalk virus (NV) by a 2 mg/L dose of pre-formed monochloramine was determined at pH 8 and 5°C in bench-scale, batch disinfection experiments using quantitative RT-PCR for NV assays. Two other enteric viruses, poliovirus 1 (PV1) and coliphage MS2, were included for comparison and assayed by infectivity as well as RT-PCR. After 3h, reductions of PV1 and MS2 by infectivity assays were about 1 log10 but there were no reductions of these viruses by RT-PCR assays. Hence, RT-PCR underestimated viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
33
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 0 publications
1
33
1
Order By: Relevance
“…Shin and Sobsey 1998;Thurston-Enriquez et al 2003). However, several studies have concluded that viral particle-association has an adverse effect on chemical disinfection.…”
Section: Case Studies Of the Chemical Disinfection Of Particle-assmentioning
confidence: 99%
“…Shin and Sobsey 1998;Thurston-Enriquez et al 2003). However, several studies have concluded that viral particle-association has an adverse effect on chemical disinfection.…”
Section: Case Studies Of the Chemical Disinfection Of Particle-assmentioning
confidence: 99%
“…Their ability to withstand current drinking water disinfection practices is largely unknown, since there are no known animal or mammalian cell culture systems that determine NV infectivity. Due to these difficulties, two alternative studies, a human feeding study and a PCRbased study, were carried out previously (30,41). However, conflicting results between these studies made conclusions regarding NV chlorine resistance difficult.…”
mentioning
confidence: 99%
“…Chlorine inactivation studies have demonstrated the susceptibilities of important enteric viruses that have threatened or caused waterborne outbreaks, such as polio virus (5,38,40) and hepatitis A virus (HAV) (17,43). Based on previous viral disinfection studies, the EPA published the Guidance Manual for Compliance with the Filtration and Disinfection Requirements for Public Water Sources (EPA Guidance Manual) (45).…”
mentioning
confidence: 99%
“…Their ability to withstand current drinking water disinfection practices is largely unknown, since there are no known animal or mammalian cell culture systems that determine NLV infectivity. Due to these difficulties, two studies, a human feeding study and a PCRbased study, have been carried out previously (29,40). Conflicting results, however, between these studies make conclusions regarding NLV chlorine resistance difficult.…”
mentioning
confidence: 99%
See 1 more Smart Citation